BONE ANATOMY OF THE PECTORAL GIRDER GIRDLES, THORACIC LIMB, PELVINA WAIST AND PELVINO LIMB OF Chellus fimbriatus (SCHNEIDER, 1783) (Reptilia: Chelidae) - Romão, Mariluce Ferreira; Santos, André Luiz Quagliatto; Silva, Thaís Aparecida (Brazilian Journal of Implantology and Health Sciences, 2023)
Testudines or queloniums generally have similar morphological characteristics. Chelonians belong to the group of reptiles, to the subclass Anapsidia, as well as to the order Chelonia or Testudinata. Chellus fimbriatus (Schneider 1783) is a typical South American turtle, and popularly known as mata-mata. It is a species considered exotic, in view of its external appearance, with projections in fibrillated or nailed. Differentiated skin helps, very much, in camouflage in the middle of its native environment. The ostheology of the pectoral and pelvina waist, as well as the zeugopodium, stylepodium and autopodium of the thoracic and pelvino limb of Chellus fimbriatus, present similar patterns in relation to testudines in general. The most prominent morphological difference refers to the skin with nailed or fibrillated projections. Above all, it is important to highlight that the knowledge of the anatomy of wild animals favors the interventions of veterinarians, since it makes possible more assertive actions, which result in better prognoses, in addition to greater longevity of these animals.